Kota Pulau Abad-21 : Tantangan Perencanaan Pembangunan Kota Sofifi sebagai Kawasan Khusus Ibukota Provinsi Maluku Utara - Ghefira Nurul Qolbi; Heru Nurasa; Mas Halimah (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2022)
The purpose of this paper is to provide a general description of Sofifi's condition which will serve as a Special Capital Region of North Maluku Province. In this case, Ternate, which is the temporary capital of North Maluku, is placed as the city center, as if forgetting Sofifi as the official capital of North Maluku Province. After nearly 22 years, the discourse of moving the capital city of North Maluku Province from Ternate to Sofifi has come to light. This year, the central government plans to make Sofifi a special area to support its readiness to make the transition to moving the provincial capital. In this writing, the method used is literature study in the form of journals, scientific literatures, books, news, and so on. The analysis used in this research is qualitative. The definition of qualitative research itself is research that produces descriptive data regarding spoken and written words, and observable behavior of the people being studied. In qualitative research, the research process is carried out continuously so that the stages of data collection, data processing, and data analysis are carried out simultaneously during the research process. Therefore, the data used, especially in this writing, are in the form of descriptive word descriptions